Sociological and Philosophical Study of Ijārah and Ijārah Muntahiya bi Tamlik - Novita Angraeni; Erry Fitrya Primadhany (Institut Agama Islam Negeri Palangka Raya, 2022)
Mu’āmalah is a matter that is constantly evolving following the progress of the times, including the ijārah contract and the ijārah muntahiya bi tamlik contract. It is necessary to study sociological and philosophical perspectives to obtain a deep meaning regarding the contextual aspects. This research was normative research that examines the norms and principles of Islamic law as well as developing doctrines that are relevant to the theme of the study. The approach was a conceptual approach which intended to analyze the concepts in Islamic law to find out the meaning. Ijārah is a contract for the transfer of usufructuary rights over an item or service and ijārah muntahiya bi tamlik is a lease agreement with the option of transferring ownership rights. The legal basis of the ijārah agreement and the ijārah muntahiya bi tamlik was found in the Qur'an, Hadith and several regulations. Sociological studies of the ijārah and ijārah muntahiya bi tamlik contracts include that the ijārah and ijārah muntahiya bi tamlik aim to facilitate humans in carrying out their lives and can synergize with each other to meet the needs of life. And containing orders to fulfill individual rights can also bring prosperity and peace to those who implement it. From a philosophical point of view, it contains values sourced from the Qur'an and hadith in the form of values of justice and universal principles and has the goal of benefiting mankind and avoiding harm.